DISASTER-RISK MANAGEMENT OF CARAL WORLD HERITAGE SITE, PERU - Jigyasu, Rohit; Vargas, Julio (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Vulnerability of World Heritage Properties is increasing, leading to serious and irreversible damage due to natural and human induced disasters. There are many World Heritage properties located in seismic areas, such as the Peruvian region, where the 5000-yearold archaeological site of t he Sacred City of Caral is located. The seismic risk of the site is speciically high due to vulnerability of earthen heritage to earthquakes. Receiving the support of the US Ambassadors Fund for Cultural Preservation, a multidisciplinary team, including conservators, architects and structural engineers, was established during recent conservation works to conduct stud ies on soil mechanics and geodynamics by using state-of-the-art tools. A team of structural engineers working through coordination between various ield and ofice activities performed an assessment of the structural vulnerability of a typical ancient pyramid. The interdisciplinary team selected this pyramid on the basis of its size and conservation conditions. The results of this study showed that the organized and reinforced core of the pyramid is very stable compared to the scaled platforms of the pyramids, which are not really part of the structure. Considering this challenge, important changes were recommended in the retroitting methodology. Recurrent earthquakes have led to the collapse of many façades in the past, exposing the core vegetal-iber reinforcement to ultraviolet rays, thereby reducing the ibers’ tensile capacity that was controlling the stability, and also leading to the collapse of the core structure during earthquakes. In order to protect this important heritage site from future disasters, the paper will describe-preventive conservation strategies, prioritized through an action plan. This paper will also describe basic principles, methodology and activities for a comprehensive risk-management plan for Caral World Heritage Site that takes into account mitigation, emergency response and recovery and integrates it into the overall management of the Archaeological Site of Caral.